A new specimen of the Early Cretaceous long-necked choristodere Hyphalosaurus from Liaoning, China with exceptionally-preserved integument. (April 2023) - Wang, Miaoyan; Xing, Lida; Niu, Kecheng; Liang, Qingqing; Evans, Susan E.
Abstract: Although the highly specialized long-necked Early Cretaceous choristodere Hyphalosaurus is well known from the Jehol Biota of China, the integument of this genus has been only partially described. A new specimen from Liaoning Province, China, attributed to the species H. lingyuanensis, reveals additional details. The integumentary remains demonstrate a variety of scale shapes including rhomboid, square, rectangular, polygonal, and round-to-ovoid scales. The latter are arranged in parasagittal rows along the flanks and tail, but not along the neck. These rows of enlarged scales resemble the pattern seen in the contemporaneous short-necked Chinese Monjurosuchus splendens and may be a shared derived trait. In addition, carbonaceous films between the phalanges support the view that the manus and pes were partially webbed in Hyphalosaurus, as in Monjurosuchus and many other aquatic reptiles. The new specimen thus provides further insights into the life appearance of Hyphalosaurus .